Determinants of time limit at velocity corresponding to VO2max in physically active individuals - Leonardo Gonçalves Ribeiro; Tony Meireles dos Santos; Jorge Roberto Perrout de Lima; Jefferson da Silva Novaes (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n1p69 The objective of the present study was to determine the relationship between time limit (Tlim) at VO2Máx velocity (VVO2Máx) and the variables VO2Máx, VVO2Máx, running economy (RE), ventilatory threshold (VT), strength test (9-10 maximum repetitions), velocity at maximal anaerobic running test (VMART), vertical jump test and body fat percentage. The sample was composed of 18 male volunteers, aged between 18 and 45 years old, non-athletes, but physically active. The study was carried out during fi ve visits, on non-consecutive days and at approximately the same time each day: visit 1 - signature of informed consent form, medical history, anthropometric assessment, aerobic power test and familiarization with Tlim test; visit 2 - RE test and Tlim test; visit 3 - familiarization with VMART test; visit 4 - familiarization with vertical jump and 9-10 maximum repetition tests and VMART test; visit 5 - vertical jump and 9-10 maximum repetition tests. Low (r = 0.220 to - 0.359) and non-signifi cant correlations (p = 0.281 to 0.935) were observed between Tlim and the selected variables, characterizing the low predictive value of Tlim for the sample studied. Thus, and because of the considerable inter-individual variability in Tlim, no variable was identifi ed that was capable of satisfactorily predicting Tlim.